MODUL KETERAMPILAN BICARA BAHASA ARAB MENGGUNAKAN MEDIA KOTAK SAKU - Achmad Robith Khusni; Hasan Aziz (Lahjah Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2021)
The Researchers see that the Arabic learning system at MTS Sirojut Tholibin is soo monotonous, only conveys what is in books and teaching materials and does not have a model or strategy in learning. While the purpose of this media is as additional basis and motivation so that students are more enthusiastic and creative in learning Arabic, especially Arabic in speaking skills. So the easy solution is that researchers will create modules or teaching materials based on Bithoqoh Jaybiyah, which is a pocket box for Arabic vocabulary. The Qualitative descriptive analysis approach with preliminary research using a defined and designed development model. This analysis will produce an Arabic vocabulary pocket box product for each student.